Na geografia do traço, o compasso literário - doi: 10.4025/actascilangcult.v34i1.13135 - Barzotto, Leoné Astride (Acta Scientiarum. Language and Culture, 2011)
PEPETELA. O planalto e a estepe. São Paulo: Leya, 2009. 188 p. ISBN 9788562936098.